Nitrogen Helps the Cultivator Working of the Organs of the Sirted Coating, Harvest Sharing, Learning Microstructures (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article examines the structural and phase changes in surface diffusion nitride-oxide coatings obtained during nitriding in a gas environment followed by oxidation of ferrite-pearlite steels in water vapor, as well as the influence of phase changes on the corrosion properties.